2021
DOI: 10.1016/s0140-6736(21)00675-9
|View full text |Cite|
|
Sign up to set email alerts
|

SARS-CoV-2 infection rates of antibody-positive compared with antibody-negative health-care workers in England: a large, multicentre, prospective cohort study (SIREN)

Abstract: Background Increased understanding of whether individuals who have recovered from COVID-19 are protected from future SARS-CoV-2 infection is an urgent requirement. We aimed to investigate whether antibodies against SARS-CoV-2 were associated with a decreased risk of symptomatic and asymptomatic reinfection. Methods A large, multicentre, prospective cohort study was done, with participants recruited from publicly funded hospitals in all regions of England. All health-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
481
8
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 605 publications
(551 citation statements)
references
References 41 publications
(34 reference statements)
37
481
8
4
Order By: Relevance
“…For simplicity, we assume random mixing within a population, seropositivity as a perfect marker of immunity, and that natural immunity is fully sterilising (stops onward transmission). This is based on observations that seropositivity is associated with at least a 0.84 (95% CI: 0.81–0.87) reduction in risk of reinfection [ 10 ], and reinfections are likely to in turn be less infectious [ 11 ]. As seropositivity from natural infection is likely to be concentrated among groups more involved in transmission (i.e.…”
Section: Sars-cov-2 Seroprevalence As a Proxy For Natural Immunitymentioning
confidence: 99%
“…For simplicity, we assume random mixing within a population, seropositivity as a perfect marker of immunity, and that natural immunity is fully sterilising (stops onward transmission). This is based on observations that seropositivity is associated with at least a 0.84 (95% CI: 0.81–0.87) reduction in risk of reinfection [ 10 ], and reinfections are likely to in turn be less infectious [ 11 ]. As seropositivity from natural infection is likely to be concentrated among groups more involved in transmission (i.e.…”
Section: Sars-cov-2 Seroprevalence As a Proxy For Natural Immunitymentioning
confidence: 99%
“…Some regions, such as the city of Pune, where serosurveys showed that more than 50% of the population had been infected in the first wave, are currently showing many cases in the second wave. 43 This sharp rise could be due to a confluence of factors, such as the potential effect of waning immunity (recent studies show 84% protection at 7 months from past infections), 44 new variants of concern, mass gatherings due to election campaigns, festivities, religious congregations, the reopening of the crowded public transportation system, as well as a sense of false security in the public that has led to a relaxation of preventive measures like face covering and social distancing. While the daily test positivity rate stayed below 2% for much of the period since October 2020, it is currently at 7.2% on March 30, 2021 (covind19.org 5 ).…”
Section: Myths Unsupported By Data and Models Overstretching Limited Datamentioning
confidence: 99%
“…In this prospective longitudinal cohort study, healthcare workers have been sampled every two to four weeks over a 12-month period [ 73 ]. Over the period 18 June 2020 to 31 December 2020, a total of 30,625 participants had been enrolled and an 84% protective effect resulting from past infection reported [ 74 ]. In a separate study (VIVALDI), the extent of SARS-CoV-2 infection has been investigated for long term care facilities and follow-up testing of care home residents and staff has been performed to estimate the protective effect of SARS-Cov-2 infection [ 75 ].…”
Section: Population Antibody Screening For Sars-cov-2 Infection Undertaken By the Uk Government In Englandmentioning
confidence: 99%